Dental Awareness, Knowledge and Attitude among the Medical Practitioners in Pokhara, Nepal - Manandhar, A.; Bhandari, A.; Kunwar, D. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Oral health is a window to our overall health. Negligence to oral health might have adverse effects on the general well being of a person. Hence, early detection and prompt treatment is of utmost importance. Lack of general medical practitioner’s knowledge of oral disease has been shown to contribute to delays in referral and treatment, thus significantly affecting the associated morbidity and mortality.Methods: The present study was undertaken to assess knowledge, attitude and dental awareness among medical practitioners in Pokhara, Nepal. A list of medical practitioners was obtained from the NMA (Nepal Medical Association, Gandaki branch, Nepal) and sample size of 109 study subjects was calculated. A cross-sectional study was conducted among the medical practitioners. from March 2018 to April 2018. The data pertaining to their knowledge, attitude and awareness about oral health was gathered using a self-administered questionnaire. The data was analyzed using descriptive statistics.Results: Results of the study showed that the medical practitioners had moderate to good knowledge about dentistry as 97.2% of the medical practitioners answered correctly saying that brushing tooth daily prevents tooth decay and periodontal disease Whereas, when asked about the changes in the oral cavity which most commonly is associated with progression towards oral cancer, only 46.8% answered correctly by responding to non-healing ulcer/ erosive lesions.Conclusions: It is imperative that the dental/medical practitioners have good knowledge about the oral diseases and its systemic manifestations, so as to have timely referral and early treatment to prevent the associated morbidity and mortality.